The Roma of Romania during World War II - Achim, Viorel (Balcanica Posnaniensia. Acta et studia, 2001)
The article presents the situation of the Roma population in Romania during the rule of Marshal Ion Antonescu and examines the deportation of Roma to Transnistria during the Second World War. The author aims to reconstruct Romanian state policy toward the Roma and to reassess previous estimates concerning the scale of persecution suffered by this group. The study is based on the analysis of archival documents, administrative records, and statistical sources. The author points out that before the Second World War, the Roma were not regarded by the Romanian state as a conventional national minority but rather as a social group existing on the margins of public life. Unlike the Jews, they were not subjected to systematic discriminatory policies during the interwar period. The situation changed after the Antonescu regime came to power, when the so-called “Gypsy question” emerged. The author analyzes the processes of identifying, classifying, and deporting Roma to Transnistria, paying particular attention to the motives of the authorities and the actual scale of repression. Special significance is attached to the critical reassessment of earlier estimates regarding the number of victims and the size of Romania’s Roma population. The conclusions indicate that the deportations formed part of a broader ethnic policy pursued by the Romanian state during the war and had lasting consequences for the development of the Roma community after 1945.